Nutrition Policy and Governance in Ethiopia: What Difference Does 5 Years Make?. Issue 4 (December 2020) - Kennedy, Eileen; Mersha, Girmay A.; Biadgilign, Sibhatu; Tessema, Masresha; Zerfu, Dilnesaw; Gizaw, Rahel; Kershaw, Meghan
Two studies, ENGINE (Empowering New Generations to Improve Nutrition and Economic opportunities) and Growth through Nutrition, were conducted in the same 4 regions of Ethiopia approximately 5 years apart. A similar protocol using a quantitative and qualitative survey of key informants at the subnational level was used to explore barriers and facilitators for implementation of the country's national multisector nutrition plan. Noticeable differences were observed, including a change in the perception of the nutrition problems in pregnant women and preschool aged children and greater awareness of the multisector plan. Poor coordination and collaboration were still noted in both time periods. A key issue highlighted was the need to keep up the momentum for multisector approaches to improve nutrition in the policy agenda.